From Love Jihad to Grooming Gangs: Tracing Flows of the Hypersexual Muslim Male through Far-Right Female Influencers - Eviane Leidig (Religions, 2021)
This article traces the transnational flows of constructions of the hypersexualized Muslim male through a comparative analysis of love jihad in India and the specter of grooming gangs in the UK. While the former is conceived as an act of seduction and conversion, and the latter through violent rape imaginaries, foregrounding both of these narratives are sexual, gender, and family dynamics that are integral to the fear of demographic change. Building upon these narratives, this study analyzes how influential women in Hindu nationalist and European/North American far-right milieus circulate images, videos, and discourses on social media that depict Muslim men as predatory and violent, targeting Hindu and white girls, respectively. By positioning themselves as the daughters, wives, and mothers of the nation, these far-right female influencers invoke a sense of reproductive urgency, as well as advance claims of the perceived threat of, and safety from, hypersexualized Muslim men. This article illustrates how local ideological narratives of Muslim sexuality are embedded into global Islamophobic tropes of gendered nationalist imaginaries.